2022
DOI: 10.3390/insects13050432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intestinal Microbial Diversity of Four Species of Grasshoppers and Determination of Cellulose Digestibility

Abstract: Grasshoppers (Insecta, Orthoptera, Acridoidea) are a large group of agricultural and animal husbandry pests. They have a large food intake with high utilization of plants fibers. However, the composition of the grasshopper gut microbial community, especially the relationship between gut microbial community and cellulose digestibility, remains unclear. In this research, 16S rRNA gene sequences were used to determine the intestinal microbial diversity of Acrida cinerea, Trilophidia annulata, Atractomorpha sinens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…This further suggests that grasshoppers can predict changes in their gut microbiota throughout their life history. This study found that Firmicutes and Proteobacteria dominated all life stages in the gut of Locusta migratoria , similar to previous studies on other adult grasshoppers under field conditions, includingSphingonotus mongolicus (Bai et al, 2022), Oedaleus decorus (Ling et al, 2022), Desert locust (Dillon et al, 2002). Firmicutes and Proteobacteria are also the main phyla of other insects, including Praying mantis , Anopheles bicolor ,Rainbow stag beetle , Holotrichia parallela, andBurying beetle (Berasategui et al, 2016;Huang et al, 2012;Vogel et al, 2017;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…This further suggests that grasshoppers can predict changes in their gut microbiota throughout their life history. This study found that Firmicutes and Proteobacteria dominated all life stages in the gut of Locusta migratoria , similar to previous studies on other adult grasshoppers under field conditions, includingSphingonotus mongolicus (Bai et al, 2022), Oedaleus decorus (Ling et al, 2022), Desert locust (Dillon et al, 2002). Firmicutes and Proteobacteria are also the main phyla of other insects, including Praying mantis , Anopheles bicolor ,Rainbow stag beetle , Holotrichia parallela, andBurying beetle (Berasategui et al, 2016;Huang et al, 2012;Vogel et al, 2017;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“… Wang et al (2020) determined the cellulose digestibility of three species of grasshoppers, Aiolopus tamulus , Oedaleus decorus asiaticus , and Shirakiacris shirakii , to wheat at 43.95, 38.01, and 44.12%, respectively, and the hemicellulose digestibility of wheat at 17.21, 24.99, and 47.65%, respectively. The digestibility of four grasshopper species, Acrida cinerea , Trilophidia annulata , Atractomorpha sinensis , and Sphingonotus mongolicus , ranged from 49.87 to 67.91% for wheat, and hemicellulose digestibility ranged from 17.77 to 47.51% ( Bai et al, 2022 ). The cellulose digestibility of wheat by the four grasshopper species measured in this research ranged from 45.93 to 65.21%, which was higher than the cellulose digestibility of the above grasshoppers; the hemicellulose digestibility ranged from 7.56 to 32.41%, which was lower than the above grasshoppers.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose and xylose standard curves were plotted with reference 37 . The linear equation of glucose obtained in this experiment was y = 1.7321 x + 0.0083, R 2 = 0.9955, and the linear equation for xylose was y = 53.96 x − 0.0044, R 2 = 0.9969.…”
Section: Methodsmentioning
confidence: 99%
“…Three parallel experiments were set up for each group, and a three-tube control experiment was performed. Referring to reference 37 , the optical density (OD) values measured for each experimental group were brought to the glucose standard curve to obtain the glucose concentration, which in turn was used to calculate the cellulase activity value of each group using the following formula.…”
Section: Methodsmentioning
confidence: 99%